The events are dependent because the outcome of drawing the first card affects the outcome of the next draw. With two dependent events A and B, we also apply the Multiplication Rule:

\(P(A\ then\ B) = P(A) - P(B\ after\ A)\)

The probability that the first draw is a red card is \(38 = 3\). The probability that the second draw is a black card is now 48 (since there is no replacement). Hence, the probability of first drawing red card then a black is:

\(P( \text{red then black}) = P(red) - P(\text{black after red})\)

(ved thon black) = \(\displaystyle\frac{{1}}{{2}}\cdot\frac{{10}}{{19}}\)

P(red then black) = \(\displaystyle\frac{{5}}{{19}}\)